Stress Oximetry: Description of a Test to Determine Readiness for Discontinuing Oxygen Therapy in Infants with Chronic Lung Disease - Naveed Hussain; Janet Schwenn; Jennifer Trzaski; Mariann Pappagallo (Hindawi Limited, 2018)
Background. In infants with CLD there are no objective tests to monitor an infant's progress towards weaning out of oxygen inhalation therapy (O2IT). A test involving staged maneuvers of increasing respiratory stress while decreasing oxygen support, termed Stress Oximetry (StressOx), has been used at our center for weaning O2IT. Objective. To report the clinical utility of "StressOx" in evaluating readiness for discontinuing O2IT in infants with CLD. Methods. A retrospective review was done of StressOx tests administered at our center from 2002-2008. StressOx was performed based on a consistent clinical protocol in all eligible infants on O2IT. O2IT was generally discontinued after infant had passed two StressOx tests and subsequently infants were monitored for a minimum of 7 days to determine successful weaning. Results. There were 279 infants with 899 tests that met inclusion criteria. An average of 3 tests per infant was done, one week apart. The test had a specificity of 97.4% and a positive predictive value of 99.6% in determining success of discontinuing O2IT. Conclusions. StressOx appears to be a clinically useful test that may help in determining an infant's ability to successfully wean out of O2IT. Further validation of this test is warranted.